Design and implementation of a pedagogical strategy that fostered the knowledge of pregnant women about breastfeeding and its relationship with dental and maxillofacial development at Santa Mónica Hospital (Dosquebradas, Risaralda) during 2017 (Revista Nacional de Odontología, 2019)
Introduction: the literature reports the favoring of breastfeeding in anteroposterior maxillary growth and in the development of the masticatory apparatus, as it avoids deforming habits and improves dental occlusion. Objective: to design and implement a pedagogical strategy that promotes the knowledge of pregnant wo-men about breastfeeding and its relationship with the dental and maxillofacial development at Santa MónicaHospital (Dosquebradas, Risaralda, Colombia) during 2017. Methodology: qualitative approach, research-action method, with population of pregnant women at Santa Mónica Hospital; a non-probabilistic sample was implanted for convenience, and the sample was 16 pregnant women. As techniques, participant observation and the focus group were employed, at the same time as pedagogical strategies were applied; field journals and transcription of focal group recordings were used. The information was analyzed and categories and subcategories were obtained, establishing an open coding and an axial codification. Finally, a comparison was made between the transcripts from the initial and final focal groups. Results:it was evidenced that the initial knowledge was low and the participants were unaware of the relations-hip between breastfeeding and dentomaxillofacial development in children. In the pedagogical strategy, this relationship was approached and, in the final focus group, the acquisition of new knowledge was demonstrated. Conclusion: the pedagogical strategies that link the active participation of pregnant women promote the ac-quisition of new knowledge related to the good practices of breastfeeding and its impact on the dental andmaxillofacial development of children
Keywords: breastfeeding; strategies; pedagogy; community participation; pregnant women; maxillofacial development